Postpartum analgesia - Bachmann Sánchez, Carlos (2015)
The clinical study was conducted Pentozacina powerful painkiller orally, in the immediate postpartum period 150 women admitted to the Maternity Hospital of Lima. It was a double-blind, random study that Darvon Compound as control substance and talc was used as placebo. The results were qualitatively very flattering for the pentazocine that pain relief was much more evident especially in severe pain. Quantitatively, no significant difference was found with its similar.